Diatoms as a proxy in reconstructing the Holocene environmental changes in the south-western Baltic Sea: the lower Rega River Valley sedimentary record - Witkowski, Andrzej; Cedro, Bernard; Kierzek, Agnieszka; Baranowski, Damian (Hydrobiologia, 2009)
This study focuses on diatom assemblages occurring in cores of Late-glacial and Holocene deposits retrieved from the mouth of the lower Rega River valley, of the southern coast of the Baltic Sea. Sediment samples from four cores were the subject of the present study. Diatom-inferred environmental characteristics, e.g., water level; water salinity (conductivity), trophic status and pH, within each core are presented. Diatom assemblage zones (DAZ) were distinguished, based on differences in the distribution of particular ecological groups. Each DAZ appears to be related to environmental changes during the deposition of a given sediment interval. The Late-glacial (Allerød) sediments originated in a shallow lake with increasing concentrations of solutes and nutrients. The Holocene record begins in the early Atlantic Chronozone and the diatoms point to weakly brackish-water sediments deposited in a shallow water environment. During the period of 8,500-5,800 cal year BP sedimentation took place in a shallow embayment and/or lagoon. From ca. 5,800 cal year BP onwards sedimentation took place in a peat bog environment alternating with Aeolian deposition. Changes in diatom community structure imply a close relationship with the climate-controlled eustatic rise of the ocean level and its consequence Littorina transgression. As with other southern Baltic Sea localities, brackish-water diatoms appear in the sediments, signaling the onset of marine transgression somewhat earlier than previously accepted. Differences and similarities in diatom assemblages and the palaeogeographic development of nearby regions within the Baltic Sea basin and lagoons (coastal areas) from different geographic regions, are also discussed.